2004
DOI: 10.1093/toxsci/kfh035
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cell-Mediated Immune Responses to Listeria Infection by Repeated Exposure to Diesel Exhaust Particles in Brown Norway Rats

Abstract: Diesel exhaust particles (DEP) have been shown to alter pulmonary immune responses to bacterial infection. Exposure of rats to 100 mg/m(3) DEP for 4 h was found to aggravate Listeria monocytogenes(Listeria) infection at 3 days postinfection, but the bacteria were largely cleared at 7 days postinfection due to the development of a strong T cell-mediated immunity. In the present study, we examined the effects of repeated DEP exposure at lower doses on pulmonary responses to bacterial infection. Brown Norway rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 39 publications
3
38
0
1
Order By: Relevance
“…17 Repeated low-dose DEP exposure resulted in downregulation of T cell-mediated immune responses, whereas a single high-dose exposure to DEPs aggravated bacterial infection and triggered strong T cell-mediated immunity, indicating that DEPs can also alter pulmonary immune responses to bacterial infection. 31 Individuals with gene variants for phase II detoxifying enzymes (glutathione-s-transferase P1 and M1), causing the absence or reduced production of these enzymes, have been demonstrated to have increased susceptibility …”
Section: Diesel Exhaust Particulate Mattermentioning
confidence: 99%
“…17 Repeated low-dose DEP exposure resulted in downregulation of T cell-mediated immune responses, whereas a single high-dose exposure to DEPs aggravated bacterial infection and triggered strong T cell-mediated immunity, indicating that DEPs can also alter pulmonary immune responses to bacterial infection. 31 Individuals with gene variants for phase II detoxifying enzymes (glutathione-s-transferase P1 and M1), causing the absence or reduced production of these enzymes, have been demonstrated to have increased susceptibility …”
Section: Diesel Exhaust Particulate Mattermentioning
confidence: 99%
“…However, a study conducted in Chile by Ruiz et al (42) found no association between ambient air pollution and the humoral immune system in children. Emerging evidence from animal toxicological studies suggest that ambient air pollution may cause suppression of host immunity (43,44).…”
Section: Altered Immunitymentioning
confidence: 99%
“…Although other inflammatory disorders, such as chronic alcoholism 5 and particulate matter inhalation, 6 have been linked with AM dysfunction, AM function has not been extensively evaluated in asthma. Recently, increased AM activation and decreased phagocytosis of apoptotic cells were reported in asthmatic adults.…”
mentioning
confidence: 99%